The Relationship between Religiosity and Academic Performance amongst Accounting Students - Umaru Mustapha Zubairu; Olalekan Busra Sakariyau (Institute of Advanced Engineering and Science, 2016)
In this paper, the association between religiosity and academic performance among accounting students enrolled at the International Islamic University Malaysia (IIUM) is explored, as recent research demonstrates a positive association between religiosity and academic success. Students' religiosity was measured using proxies from an Islamic perspective, whilst their academic performances were measured using their Cumulative Grade Point Averages (CGPA). The statistical analysis revealed no significant correlation between religiosity and academic performance among accounting students at IIUM. However, a closer examination of the results revealed that students at IIUM possessed high levels of religiosity as well as high levels of academic performances.